Cardiopulmonary Responses to Sub-Maximal Ergometer Exercise in a Hypo-Gravity Analog Using Head-Down Tilt and Head-Up Tilt - Diaz-Artiles, Ana; Navarro Tichell, Patricia; Perez, Francisca (Frontiers in Physiology, 2019)
After more than 50 years of spaceflight, we still do not know what is the appropriate range of gravity levels that are required to maintain normal physiological function in humans. This research effort aimed to investigate musculoskeletal, cardiovascular, and pulmonary responses between 0g and 1g. A human experiment was conducted to investigate acute physiological outcomes to simulated altered-gravity with and without ergometer exercise using a head-down tilt (HDT)/head-up tilt (HUT) paradigm. A custom tilting platform was built to simulate multiple gravitational loads in the head-to-toe direction (Gz) by tilting the bed to the appropriate angle. Gravity levels included: Microgravity (−6°HDT), Moon (0.17g-Gz at +9.5ºHUT), Mars (0.38g-Gz at +22.3ºHUT), and Earth (1g-Gz at +90º upright). Fourteen healthy subjects performed an exercise protocol at each simulated gravity level that consisted of three work rates (50W, 75W, 100W) while maintaining a constant cycling rate of 90 rpm. Multiple cardiopulmonary variables were gathered, including volume of oxygen uptake (VO2), volume of carbon dioxide output (VCO2), pulmonary ventilation (VE), tidal volume (VT), respiratory rate (Rf), blood pressure, and heart rate (HR) using a portable metabolic system and a brachial blood pressure cuff. Foot forces were also measured continuously during the protocol. Exercise data were analyzed with repeated-measures ANOVA with Bonferroni correction for multiple comparisons, and regression models were fitted to the experimental data to generate dose-response curves as a function of simulated AG-levels and exercise intensity. Posture showed a main effect in all variables except for systolic blood pressure. In particular, VO2, VCO2, VE, VT, Rf, and HR showed average changes across exercise conditions between Microgravity and 1g (i.e. per unit of simulated AG) of −97.88 mL/min/g, −95.10 mL/min/g, −3.95 L/min/g, 0.165 L/g, −5.33 breaths/min/g, and 5.05 bpm/g, respectively. In the case of VO2, further pairwise comparisons did not show significant differences between conditions, which was consistent with previous studies using supine and HDT postures. For all variables (except HR), comparisons between Mars and Earth conditions were not statistically different, suggesting that ergometer exercise at a gravitational stress comparable to Mars gravity ( 3/8g) could provide similar physiological stimuli than cycling under 1g on Earth.